Zebrafish motile cilia as a model for primary ciliary dyskinesia - Pinto, Andreia L. (2021)
Funding Information: Funding: This work was a product of the Project LYSOCIL funded by the European Union Horizon 2020 research and innovation under grant agreement No 811087. It received funding from Fundação para a Ciencia e tecnologia, grant PTDC/BEX-BID/1411/2014; M.R. was funded by the fellowship PD/BD/136927/2018. P.S was funded by the fellowship SFRH/BD/111611/2015; C.B. was funded by the fellowship SFRH/BD/141034/2018; SSL was funded by FCT CEEC-IND 2018. Funding Information: Acknowledgments: The authors want to thank the Fish Facility from NMS. This work was developed with the support of the Fish Facility NMS|FCM that is part of CONGENTO, a Research Infrastructure co-financed by Lisboa Regional Operational Programme (Lisboa2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (ERDF) and Fundação para a Ciência e Tecnologia (Portugal) LISBOA-01-0145-FEDER-022170. A.P. wants to thank the Royal Brompton and Harefield hospital, part of the Guy’s and St Thomas’ foundation trust, London. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.